Evaluation of Traffic Accidents in the Province of Albay: Basis for Sustainable Traffic Management Framework - Echaluce, Frande; Macabeo, Manny (JPAIR Multidisciplinary Research, 2024)
The traffic safety situation around the world is still not optimistic. Accidents occur due to a combination of factors and are rarely caused by a specific reason. Risk factors are a better explanation for why traffic accidents occur. This study determined the traffic accidents in the province of Albay. It identified the number of reported traffic accidents in the Province of Albay covering Calendar Year 2020 to 2022. It also determined the causes and risk factors of traffic accidents regarding driver’s behaviors, road conditions, vehicle conditions, traffic signs, and traffic management. Moreover, it inferred a significant agreement among the ranks regarding the causes and risk factors of traffic accidents. It proposed a traffic management framework to prevent traffic accidents in the province of Albay. The respondents of this study are 60 personnel from the three CPS in Albay, 30 from the Local Government Unit, and 47 community, representing the riders and commuters in the Poblacion area. The study revealed a concerning prevalence of traffic accidents, underscoring a pressing public concern due to the high number of casualties and severity of outcomes. Despite this, road safety has not received sufficient attention, attributed to a lack of awareness regarding the problem’s extent, associated costs, and effective interventions. Implementing a comprehensive traffic management framework involving collaboration among stakeholders is crucial for understanding and addressing the multifaceted causes of accidents, emphasizing the importance of community-wide initiatives and cooperation among various entities to enhance public awareness and promote responsible driving behavior.